A study on determinants of retirement planning: Syarikat Air Melaka Berhad (SAMB) / Nurul Izzati Mohd Zawawi and Yang Sazliza Abdul Aziz - Mohd Zawawi, Nurul Izzati; Abdul Aziz, Yang Sazliza (2014)
This study was conducted to investigate the retirement planning among Syarikat Air Melaka Berhad (SAMB). Four (4) independent variables had been identified which are goal clarity, attitude, knowledge and potential conflict. 154 respondents had participated in this study. The objectives of this study are to investigate the relationship between goal clarity, attitude, knowledge and potential conflict with retirement planning and to investigate the most contributor factor that influence to retirement planning. To ensure the objectives, researchers had use SPSS version 21. The result indicates that the significant variables that influence retirement planning are knowledge and potential conflict. Meanwhile, goal clarity and attitude have not significant on retirement planning. Besides, knowledge becomes the best predictor in retirement planning.